Length = x+5
If you were to use the FOIL rule and multiply out (x+3)(x+5), you would get x^2+8x+15
F = multiply first terms = x*x = x^2
O = multiply outer terms = x*5 = 5x
I = multiply inner terms = 3*x = 3x
L = multiply last terms 3*5 = 15
The four terms we get are x^2, 5x, 3x and 15
Add them up. Combine like terms
x^2+5x+3x+15 = x^2+8x+15
Therefore, (x+3)(x+5) = x^2+8x+15
---------------
With factoring, we think of this process in reverse
What two numbers multiply to 15 and add to 8? Those two numbers happen to be 5 and 3 which is where the (x+5)(x+3) comes from